The Correlation between Personality and Critical Thinking Ability of Junior High School Students - Eka Nurindah Sari; Baso Jabu; Kisman Salija (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This study aims to determine: (1) the students’ personalities, (2) the students’ critical thinking ability, and (3) the correlation between students’ personality and their critical thinking ability. The random sampling approach was used to choose the sample of 40 students. The instruments used were questionnaires and tests. Correlational examination with the informative plan is used to figure out the relationship between the factors and the outcome by utilizing a quantitative strategy. The study's findings suggest: (1) The personality profile of students shows a significant number of differences between thinking personality and feeling personality. Where there were more students with type thinking personality (60.5%) than feeling personality (39.5%). (2) The critical thinking ability of the students was at “Good” Level (3) Significantly negative correlations between students' personalities and critical thinking skills were found. (r -.445). The finding indicated that the higher level of personality, the lower of critical thinking ability.